Factors influencing coronary heart disease mortality: findings from the USNational Longitudinal Mortality Study - Siddaiah, Rangaswamy; Roopesh Johnson, Liaquat (International Journal of Medical Research and Review, 2016)
Introduction: Globally, mortality due to non-communicable diseases (NCDs) is on the rise. Coronary Heart Disease (CHD) is responsible for a large proportion of preventable cardiovascular mortality. This study aims to determine the factors associated with mortality due to acute and chronic CHD among adults (>18 years). Materials and Methods: A cohort of 2769 adults who died of CHD or hypertension was selected from the public-use dataset of the US National Longitudinal Mortality Study (NLMS). Age, sex, race, marital status, place of residence, health insurance status and employment status were examined for association with acute or chronic CHD mortality. Results: In bivariate analyses all variables were significantly associated with mortality due to CHD. However, in logistic regression analysis only Age (less than 70 years) (p: 0.04) and Race (White) (p: 0.001) reached statistical significance. Conclusion: Age and race are significantly associated with the occurrence of mortality due to CHD in the USA.